Comparative evaluation of fluoride release from different modifications of glass ionomer dental restorative material in primary teeth at different time intervals: An ex vivo study - Vivek Mehta; Nikhil Srivastava; Saif Ali Chaudhry; Vivek Rana (Journal of Oral Biology and Craniofacial Research)
Purpose: This ex vivo study aims to evaluate and compare the fluoride-releasing capabilities of different modifications of Glass ionomer cement, namely Giomer, Zirconomer, and Pediatric GIC (type IX) with Resin-modified Glass ionomer cement (RMGIC) in the primary dentition at first, fourteenth, and twenty-eighth days. Materials and methods: Fifty-six extracted human primary molars were allocated into four groups: Group 1, Resin-modified GIC; Group 2, Giomer; Group 3, Zirconomer; and Group 4, Pediatric GIC (type IX). The tooth samples (n = 14) were restored as per the manufacturer's instructions after making class II cavities in primary molars. Extracted tooth specimens were placed in deionized water, and the fluoride ions released were measured for 28 days. The tooth samples were evaluated for cumulative fluoride levels at the end of 24 h, 14th day, and 28th day under normal atmospheric conditions, using a fluoride ion-selective electrode (Orion STAR-A214 Ion analyzer). The data obtained was subjected to statistical analysis, and the results are discussed herein. Results: Fluoride ions releasing capability was exhibited by primary teeth restored with all the above-mentioned materials. The primary teeth restored with Zirconomer exhibited significantly higher fluoride-releasing capability among the above-compared materials, and the primary teeth restored with Giomer exhibited the least fluoride ions release on 24 h, 14th day, and 28th day, and the difference of fluoride ions releasing ability between the four groups was statistically significant at each time interval (P < 0.001). Conclusion: The primary teeth restored with Zirconomer exhibited superior fluoride-releasing ability compared to other restorative materials. Therefore, Zirconomer can be a promising restorative material for primary teeth due to its enhanced anti-caries effect.